2021
DOI: 10.3390/ijms22084286
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Factors Involved in Olfactory and Gustatory Deficits and Associations with Microbiota in Parkinson’s Disease

Abstract: Deficits in olfaction and taste are among the most frequent non-motor manifestations in Parkinson’s disease (PD) that start very early and frequently precede the PD motor symptoms. The limited data available suggest that the basis of the olfactory and gustatory dysfunction related to PD are likely multifactorial and may include the same determinants responsible for other non-motor symptoms of PD. This review describes the most relevant molecular and genetic factors involved in the PD-related smell and taste im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 224 publications
0
14
0
Order By: Relevance
“…The existence of olfactory hallucinations (phantosmia) [ 4 ], but not smell loss (anosmia), in PD patients has prompted debate and consideration about the occurrence of dysfunction in the central olfactory system. In addition, taste impairments also occur in PD patients with a frequency between 9 to 70% [ 3, 5 ], usually in the early phase of the PD pathology, that is, 2 to 10 years before the appearance of PD-related motor symptoms [ 5 ]. It is interesting to note that PD-related taste impairments in humans are mainly involved in aversive tastes, such as bitter stimuli [ 6–11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of olfactory hallucinations (phantosmia) [ 4 ], but not smell loss (anosmia), in PD patients has prompted debate and consideration about the occurrence of dysfunction in the central olfactory system. In addition, taste impairments also occur in PD patients with a frequency between 9 to 70% [ 3, 5 ], usually in the early phase of the PD pathology, that is, 2 to 10 years before the appearance of PD-related motor symptoms [ 5 ]. It is interesting to note that PD-related taste impairments in humans are mainly involved in aversive tastes, such as bitter stimuli [ 6–11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Honnes de Lichtenberg Broge et al ( 40 ) showed that despite the decline in intensity perception for everyday food odours, the liking for the food odours, especially the savoury food odours, largely remained intact. However, nine participants in this study were diagnosed with Parkinson’s disease, a degenerative disease with severe sensory disturbances ( 41 ) where olfactory impairment is a part of the clinical diagnosis ( 42 ). Flavour enhancement and aromas may, therefore, improve the palatability of meals for this group.…”
Section: Discussionmentioning
confidence: 99%
“…But the Lewy body presence in the anterior olfactory nucleus is deemed to cause loss of neurons. 28, 29 One of the reasons for olfactory dysfunction in PD is because of the misfolding of α-synuclein and its deposition occurring in the olfactory bulb and the enteric nervous system. 30 The disarrayed olfactory proteostasis affects cell survival.…”
Section: Methodsmentioning
confidence: 99%